نحو تفعيل دور المجتمع المدني لمكافحة الفساد في الدول المغاربية - شوقي, سمير (مجلة الحقوق و الحريات; No 02 (2016): مجلة الحقوق و الحريات, 2018)
نحو تفعيل دور المجتمع المدني لمكافحة الفساد في الدول المغاربية